Recent Advances in Agricultural Commodity Forecast Techniques in the Purview of Climate Change - Rahul Banerjee; Pankaj Das; . Bharti; Bulbul Ahmed (Current Advances in Geography, Environment and Earth Sciences Vol. 6, 2022)
In most of the developing and third world countries and India being no exception to it agriculture truly serves as the spine of the nation’s economy with a major percentage of the population directly involved in farming for livelihood. Climate plays one of the most significant role in almost every aspect of crop production starting from crop growth, crop development to eventually the yield of the crop. Climate also influences outbreak of crop pests and diseases and the water uptake of the crops. Possible changes in weather parameters like precipitation, temperature and CO2 concentration are anticipated to have a crucial impact on the crop growth process. Prediction of crop yield changes in the purview of changing climatic conditions can prove beneficial to the farmers in terms of devising a synchronized crop production activity as per changes in the climatic conditions. Thereby, bringing out suitable policy changes benefitting the farming community as well as the nation as a whole. In this book chapter an overview of all the statistical models and methodologies has been outlined that helps to forecast agricultural commodities under changing climatic conditions. The recent developments in the same field has also been enlisted.